Does optimism mediate the relationship between Big Five and perceived stress? A study with Spanish adolescents - Serrano, Cristina; Martínez, Paula; Murgui, Sergio; Andreu, Yolanda (Anales de Psicología / Annals of Psychology, 2021)
Research results have shown the existence of relationships between the Big Five personality factors, Optimism, and Perceived Stress. The aim of this study is to explore the possible mediating role that it has been suggested might play Optimism in this relationship. Structural equation models were conducted to examine the mediating role of Optimism. A multi-group analysis was performed to verify whether the results varied by sex. 611 Spanish adolescents completed anonymously the measures of BFQ, LOT-R and PSS. The findings showed that Optimism was positively associated with the personality traits and negatively with Perceived Stress. Perceived Stress was in turn negatively related to Emotional Stability, Extraversion and Conscientiousness, while it was not correlated with Agreeableness and Openness. Mediation analysis revealed the mediating role of Optimism on the relationship between Emotional Stability (partial mediation), Extraversion, and Conscientiousness, and the Perception of Stress. These findings did not vary by sex. In conclusion, a basic personality profile characterized by Extraversion, Emotional Stability, and Conscientiousness would favor the development of positive future expectations that represent a proximal predictor for Perceived Stress. Optimism mediation may be relevant for the development of interventions focused on reducing stress levels and, consequently, to improve the adolescent's adjustment.